Forced sterilization and abortion in Japan: Family and constitution - Yuichiro Tsuji (Bratislava Law Review, 2018)
This study analyzes the ght between the Japanese judiciary and legislature. In Japan, under the ex-Eugenic Protection Act, disabled people were obligated to undergo sterilization procedures for about 20 years. This surprising Act was established in 1948 and enabled doctors to sterilize people in order to eliminate hereditary diseases; they could also perform this procedure on physically or developmentally disabled people without their consent. The 2016 Committee on the Elimination of Discrimination against Women advised that research and compensation is urgent and necessary, but the government stated that it was a legal medical operation, and no compensation was necessary. Even under concrete judicial review, the judiciary in Japan may exercise its power to provide remedies for minorities who cannot amend statutes in the political process, or their constitutional rights will be infringed upon. is study argues that even concrete judicial reviews work to prevent serious damage before it occurs. This study will use a legal approach to review the first voting rights decision, as well as several decisions that are relevant to families in Japan. Under a concrete judicial review of the Japanese constitution, a plaintiff needs to bring a dispute in law to the court and allege that the statute or administrative disposition infringes on their human rights as provided for in the constitution. If there is no statute in the case, it is very difficult for a plaintiff to compel the legislature to pass the statute. If the legislature does not function well, the judiciary is obligated to find a way to encourage the legislature or the government to provide a remedy. The judiciary cannot compel the legislature, but may show some of the steps that it follows in its decisions.